Lipid Transfer–Dependent Endosome Maturation Mediated by Protrudin and PDZD8 in Neurons - Shirane, Michiko (Frontiers in Cell and Developmental Biology, 2020)
Endosome maturation refers to the conversion of early endosomes (EEs) to late endosomes (LEs) for subsequent fusion with lysosomes. It is an incremental process that involves a combination of endosome fusion and fission and which occurs at contact sites between endosomes and the endoplasmic reticulum (ER), with knowledge of the underlying mechanisms having increased greatly in recent years. Protrudin is an ER-resident protein that was originally shown to regulate neurite formation by promoting endosome trafficking, whereas PDZD8 is a mammalian paralog of a subunit of the yeast ERMES (ER-mitochondrial encounter structure) complex that possesses lipid transfer activity. A complex of protrudin and PDZD8 was recently found to promote endosome maturation by mediating lipid transfer at ER-endosome membrane contact sites. This review focuses on the roles of the protrudin-PDZD8 complex in tethering of endosomes to the ER, in mediating lipid transfer at such contact sites, and in regulating endosome dynamics, especially in neuronal cells. It also addresses the physiological contribution of endosome maturation mediated by this complex to neuronal polarity and integrity.